2001
DOI: 10.1063/1.1406546
|View full text |Cite
|
Sign up to set email alerts
|

High resolution x-ray spectroscopy using GaAs arrays

Abstract: We have produced a number of small format gallium arsenide (GaAs) arrays to address the material, electronic, and technological problems that need to be solved in order to develop mega pixel, Fano-limited spectroscopic x-ray imagers. Results will be presented of a series of x-ray measurements carried out on a prototype 5×5 array, fabricated from 40 μm thick epitaxial GaAs. The device has pixel sizes of 200×200 μm2 and pitch 250 μm. As a preliminary investigation of performance, two pixels have been instrumente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 14 publications
0
30
1
Order By: Relevance
“…This resulted in an energy resolution not as good as the best results achieved with GaAs p þ -i-n þ diodes with Schottky contacts and guard rings at room temperature (0.266 keV FWHM at 5.9 keV 12 and 0.300 keV FWHM at 5.9 keV 14 ). The dielectric noise was minimised in the detectorpreamplifier system reported by Owens et al 12 and Erd et al 14 by mounting both the detector and input JFET of the preamplifier in close proximity on the same low-loss substrate. It was estimated that if the dielectric noise of the additional dielectrics could be eliminated from the presently reported system, the energy resolution (FWHM at 5.9 keV) at 20 C of both spectrometers S1 and S2 would be reduced to 0.400 keV, respectively.…”
Section: B Noise Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in an energy resolution not as good as the best results achieved with GaAs p þ -i-n þ diodes with Schottky contacts and guard rings at room temperature (0.266 keV FWHM at 5.9 keV 12 and 0.300 keV FWHM at 5.9 keV 14 ). The dielectric noise was minimised in the detectorpreamplifier system reported by Owens et al 12 and Erd et al 14 by mounting both the detector and input JFET of the preamplifier in close proximity on the same low-loss substrate. It was estimated that if the dielectric noise of the additional dielectrics could be eliminated from the presently reported system, the energy resolution (FWHM at 5.9 keV) at 20 C of both spectrometers S1 and S2 would be reduced to 0.400 keV, respectively.…”
Section: B Noise Analysismentioning
confidence: 99%
“…9 Compared to Si, GaAs is more radiation hard for c-rays, electrons, low energy protons (<50 MeV 10 ), and neutrons; however, it should be noted that results have been reported showing that GaAs is less radiation hard than Si for high energy hadrons. 11 Owens et al 12,13 reported a planar 5 Â 5 GaAs p þ -i-n þ diode array structure, with a 40 lm epilayer and Au/Pt/Ti Schottky contacts at the p þ layer, which had low dark current densities (<6 nA/cm 2 ) and the best energy resolution (0.266 keV Full Width at Half Maximum, FWHM, at 5.9 keV, at room temperature) reported to date for GaAs X-ray diodes. Later devices with similar structure but thicker epilayer (325 lm) had an energy resolution of 0.300 keV FWHM at 5.9 keV, at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…10 Following this, larger devices with a thicker epilayer and similar structure to the detectors reported in Ref. 10 in a 32 Â 32 pixel array have been reported with an energy resolution of 0.3 keV FWHM at 5.9 keV at room temperature. 11 Research has also been conducted on GaAs p þ -i-n þ mesa Xray photodiodes.…”
Section: Introductionmentioning
confidence: 99%
“…A 5 Â 5 GaAs diode array structure was reported; its ultrapure epitaxial planar layer, p þ -i-n þ structure, Schottky contact at the p þ layer, and the guard ring all contributed to the low dark current densities (<6 nA/cm À2 at room temperature). 10 An energy resolution (FWHM) of 0.266 keV at 5.9 keV at room temperature was reported with these devices, after coupling them to ultra low noise front end electronics. 10 Following this, larger devices with a thicker epilayer and similar structure to the detectors reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation